Synergistic effects of photo-irradiation and curcumin-chitosan/alginate nanoparticles on tumor necrosis factor-alpha-induced psoriasis-like proliferation of keratinocytes - Clinton Gomez (2020)
© 2019 by the authors. Psoriasis is a chronic inflammatory skin disease characterized by hyperproliferation of the epidermal cells and is clinically presented as thick, bright red to pink plaques with a silvery scale. Photodynamic therapy (PDT) using visible light has become of increasing interest in the treatment of inflammatory skin diseases. In this study, we demonstrate that a combination of curcumin-loaded chitosan/alginate nanoparticles (Cur-CS/Alg NPs) and blue light emitting diodes (LED) light irradiation effectively suppressed the hyperproliferation of tumor necrosis factor-alpha (TNF-α)-induced cultured human kerlatinocyte (HaCaT) cells. The Cur-CS/Alg NPs were fabricated by emulsification of curcumin in aqueous sodium alginate solution and ionotropic gelation with calcium chloride and chitosan using an optimized formulation derived from a Box-Behnken design. The fabricated Cur-CS/Alg NPs were characterized for their particle size, zeta potential, encapsulation efficiency, and loading capacity. The surrogate 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, to measure the relative number of viable cells, showed that the CS/Alg NPs were nontoxic to normal HaCaT cells, while 0.05 µg/mL and 0.1 µg/mL of free curcumin and Cur-CS/Alg NPs inhibited the hyperproliferation of HaCaT cells induced by TNF-α. However, the Cur-CS/Alg NPs demonstrated a stronger effect than the free curcumin, especially when combined with blue light irradiation (10 J/cm2) from an LED-based illumination device. Therefore, the Cur-CS/Alg NPs with blue LED light could be potentially developed into an effective PDT system for the treatment of psoriasis.